Análises da eficácia da execução orçamentária dos Municípios da Microrregião do Seridó Oriental Potiguar (2018-2021) - Silva, Mariana Medeiros Martins da (2023)
The State's financial activity is based on the public budget, a management instrument that formalizes public policies. By expressing the government's action program in values, the public budget is consecrated as a tool that makes it possible to analyze the government's allocative choices. Effectiveness is part of the main evaluation criteria for public policies and performance and consists of achieving the intended goals and objectives. This work seeks to analyze the level of effectiveness of budget execution of the municipalities in the Seridó Oriental Potiguar microregion, from 2018 to 2021. For this purpose, data from the Budget Execution Reports were used, available on the Secretaria do Tesouro Nacional website, and effectiveness quotients were calculated. The results showed that the levels of effectiveness of the budget revenue in the municipalities of the Seridó Oriental Potiguar vary from 41.07% (Jardim do Seridó) to 117.73% (Currais Novos). The effectiveness levels of the budgetary expenditure of the municipalities in this microregion vary from 37.09% (Jardim do Seridó) to 94.99% (Cruzeta). The effectiveness levels of the financial resources used are in a percentage range with less variation, ranging from 73.15% (Ouro Branco) to 100.81% (Cruzeta). As for the levels of effectiveness in budget management, the quotients vary from 92.48% (Santana do Seridó) to 126.12% (Ouro Branco). The conclusion is that the municipalities of the Seridó Oriental Potiguar microregion have difficulties in maintaining the accuracy of revenue forecasts, which affects the realization of expenses (commitments) and ends up reflecting on the effectiveness quotients of budgetary expenditure. The effectiveness of the financial resources used shows higher quotients, which means that these municipalities do not postpone payments too much. Finally, the levels of effectiveness close to 100% in budget management indicate that these municipalities tend to carry out as many expenses as their collected revenues allow – those that exceed this percentage could commit more. The survey helps people to perceive the budget as a “quality thermometer” of elected representatives and provides useful information for the exercise of social control.